Melatonin is a potential drug for the prevention of bone loss during space flight. Issue 3 (19th July 2019) - Ikegame, Mika; Hattori, Atsuhiko; Tabata, Makoto J.; Kitamura, Kei‐ichiro; Tabuchi, Yoshiaki; Furusawa, Yukihiro; Maruyama, Yusuke; Yamamoto, Tatsuki; Sekiguchi, Toshio; Matsuoka, Risa; Hanmoto, Taizo; Ikari, Takahiro; et al.
Abstract: Astronauts experience osteoporosis‐like loss of bone mass because of microgravity conditions during space flight. To prevent bone loss, they need a riskless and antiresorptive drug. Melatonin is reported to suppress osteoclast function. However, no studies have examined the effects of melatonin on bone metabolism under microgravity conditions. We used goldfish scales as a bone model of coexisting osteoclasts and osteoblasts and demonstrated that mRNA expression level of acetylserotonin O‐methyltransferase, an enzyme essential for melatonin synthesis, decreased significantly under microgravity. During space flight, microgravity stimulated osteoclastic activity and significantly increased gene expression for osteoclast differentiation and activation. Melatonin treatment significantly stimulated Calcitonin (an osteoclast‐inhibiting hormone) mRNA expression and decreased the mRNA expression of receptor activator of nuclear factor κB ligand (a promoter of osteoclastogenesis), which coincided with suppressed gene expression levels for osteoclast functions. This is the first study to report the inhibitory effect of melatonin on osteoclastic activation by microgravity. We also observed a novel action pathway of melatonin on osteoclasts via an increase in CALCITONIN secretion. Melatonin could be the source of a potential novel drug to prevent bone loss during space flight.